Gender difference in hepatic toxicity of titanium dioxide nanoparticles after subchronic oral exposure in Sprague‐Dawley rats. Issue 5 (15th January 2019) - Chen, Zhangjian; Zhou, Di; Zhou, Shupei; Jia, Guang
Abstract: Existing literature pointed out that the liver may be the target organ of toxicity induced by titanium dioxide nanoparticles (TiO2 NPs) via oral exposure. Gender differences in health effects widely exist and relevant toxicological research is important for safety assessment. To explore the gender susceptibility of TiO2 NP‐induced hepatic toxicity and the underlying mechanism, we examined female and male Sprague‐Dawley rats administrated with TiO2 NPs orally at doses of 0, 2, 10 and 50 mg/kg body weight per day for 90 days. The serum biochemical indicators and liver pathological observation were used to assess hepatic toxicity. We found significant hepatic toxicity could be induced by subchronic oral exposure to TiO2 NPs, which was more obvious and severe in female rats. No accumulation of TiO2 NPs in the liver was observed, indicating that hepatic toxicity may not be caused through direct pathways. Oxidized glutathione, lipid peroxidation products increased significantly and reduced glutathione decreased significantly in the liver of rats in repeated TiO2 NP‐exposed groups. Hematological parameters of white blood cells and inflammatory cytokines in serum including interleukin 1α, interleukin 4 and tumor necrosis factor also increased significantly. Indirect pathways through initiating oxidative stress and inflammatory responses were suggested as the possible mechanism of the hepatic toxicity in this experiment. The higher sensitivity to redox homeostasis imbalance and inflammation of female rats may be the main reason for gender differences. Our research suggested that gender should be a susceptible factor for identifying and monitoring long‐term oral toxicity of TiO2 NPs. Abstract : We conducted an animal study to explore the gender difference in hepatic toxicity of titanium dioxide nanoparticles after subchronic oral exposure. We found significant hepatic toxicity could be induced by subchronic oral exposure to titanium dioxide nanoparticles, which was more obvious and severe in female rats. Indirect pathways through initiating oxidative stress and inflammatory responses were suggested as the possible mechanism of the hepatic toxicity. The higher sensitivity to redox homeostasis imbalance and inflammation of female rats may be the main reason for gender differences.